An investigation into the effects of role-play on efl students' speaking ability at Vo Van Kiet high school in Rach Gia - Nguyễn Thị Mỹ Ngân (Trường Đại học Trà Vinh, 2020)
Until now, there have been many researchers studying the effects of role play on students’ English speaking ability in the world and in Vietnam. However, there has been no research conducted at Vo Van Kiet high school.